A percepção dos coordenadores de área sobre o impacto do PIBID na formação inicial de licenciandos do curso de pedagogia - Matos, Marta Juliana Jordão de (2017)
The present investigation has as object of study the impact of the PIBID in the initial formation of teachers. The Program is coordinated by the Coordination for the Improvement of Higher Education Personnel (Capes), which, since 2007, through Law No. 11,502, began to work in the training of teachers of basic education, subsidizing the Ministry of Education (MEC) In the elaboration of policies that contribute to the training of teaching professionals for basic and higher education. In this context, the general objective of this research is to verify the perception that the coordinating teachers of an institution of higher education of the metropolitan region of São Paulo, acting in the Pedagogy course of said institution, on the impact of the PIBID in the initial formation of graduates of the Course of Pedagogy. To listen to such subjects and to make placements about their statements has as a projection the answer to the following questions: boasted as a fundamental figure in PIBID, has the CA developed actions that go towards achieving the objectives proposed by the program? Does he realize and carry out his duties as an articulator of dialogue between theory and practice in the initial formation of sachets? How do you understand your actions contribute to this? How do you perceive and operationalize the relationships between the other actors in the program? In order to pursue such proposals, a qualitative research methodology was chosen in this research composed of a bibliographical survey on the subject and semi-structured interviews.